Analisis Hubungan Riwayat Keluarga dan Aktivitas Fisik dengan Kejadian Hipertensi di Kelurahan Indrasari Kabupaten Banjar - Elsi Setiandari L.O; Ari Widyarni; Aulia Azizah (Universitas Batanghari Jambi, 2020)
Hypertension is a condition in which a person has an increase in blood pressure above normal as indicated by the systolic and diastolic numbers on blood pressure checks using a blood pressure measuring device. The incidence of hypertension in Southeast Asia is 24.7% and 23.3% of Indonesia's population. The results of the initial survey of blood pressure measurements and interviews obtained the results of blood pressure checks from 30 community members with the criteria not suffering from hypertension as many as 3 people and those suffering from pre-hypertension were 9 people and those suffering from hypertension were 18 people. The purpose of this study was to determine the analysis of the relationship between family history and physical activity with the incidence of hypertension in Indrasari Village, Banjar Regency. This research was conducted with an analytic observational research design and method cross sectional. The population in this study were all hypertension sufferers in Indrasari who met the criteria as many as 87 people. Data analysis used univariate analysis using frequency distribution and bivariate analysis using chi-square test. The results showed that from the results of the chi square test, there was correlation between family history, physical activity and the incidence of hypertension , the value was obtained p = 0.001 <α 0.005 and the value obtained p = 0.001 <α 0.005 was. Based on the results of the research analysis, it can be concluded that there is a relationship between family history and physical activity with the incidence of hypertension in Indrasari Village, Banjar Regency.